Visceral Leishmaniasis in a UK Toddler following a Short Trip to a Popular Holiday Destination in Spain - Neda Minakaran; Talha Soorma; Shamez N. Ladhani (Case Reports in Infectious Diseases)
We herein present the case of a 15-month-old with visceral leishmaniasis diagnosed in the UK following a short trip to a popular holiday destination in Spain. Four months after the initial symptoms, the diagnosis was made incidentally on microscopy of a bone marrow biopsy taken for suspected haematological malignancy after the child developed hepatosplenomegaly, pancytopaenia, and Klebsiella pneumoniae septicaemia.